2015
DOI: 10.5851/kosfa.2015.35.5.660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Processed Sulfur Supplementation on Texture Quality, Color and Mineral Status of Dry-cured Ham

Abstract: This study was performed to investigate the chemical composition, mineral status, oxidative stability, and texture attributes of dry-cured ham from pigs fed processed sulfur (S, 1 g/kg feed), and from those fed a basal diet (CON), during the period from weaning to slaughter (174 d). Total collagen content and soluble collagen of the S group was significantly higher than that of the control group (p<0.05). The pH of the S group was significantly higher than that of the control group, whereas the S group had a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Shear force of meat is associated with several factors such as intramuscular fat content and crosslink protein such as collagen (Wang et al , 2016). As mentioned above, the increase proteolysis index and collagen solubility of meat from the processed sulfur fed pig were reported by Kim et al (2015b).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Shear force of meat is associated with several factors such as intramuscular fat content and crosslink protein such as collagen (Wang et al , 2016). As mentioned above, the increase proteolysis index and collagen solubility of meat from the processed sulfur fed pig were reported by Kim et al (2015b).…”
Section: Resultsmentioning
confidence: 78%
“…This result was caused that NP had a decline tendency of cooking loss, whereas cooking loss of SP increased on day 3 and decreased on day 21. High collagen solubility of pork from processed sulfur fed pigs was reported by Kim et al (2015b). Kristensen and Purslow (2000) have also reported that degradation of cytoskeleton proteins such as desmin , vinculin , and talin during aging can enhance the water-holding capacity of meat due to inflow of extracellular water.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation